2017
DOI: 10.1007/s11886-017-0813-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Ischemic Mitral Regurgitation: Valve Repair Versus Replacement

Abstract: The first randomized trial to compare MV repair versus MVR in patients with severe ischemic MR, the Cardiothoracic Surgical Trials Network (CTSN) trial, was recently concluded and reported no significant difference in the primary outcome of left ventricular end systolic volume index between the two approaches at either 1- or 2-year follow-ups. Data comparing approaches of MV repair and MVR for ischemic MR is largely limited to small, non-randomized retrospective trials. The only randomized trial data to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…FMR is often treated with an annuloplasty ring that is one or two sizes smaller than the actual MA to ensure sufficient leaflet coaptation [ 23 ]. For this patient, using the actual size determined by the MA dimensions (Classic ring size 38), the simulation demonstrated improved leaflet coaptation but with a residual lateral regurgitant orifice.…”
Section: Discussionmentioning
confidence: 99%
“…FMR is often treated with an annuloplasty ring that is one or two sizes smaller than the actual MA to ensure sufficient leaflet coaptation [ 23 ]. For this patient, using the actual size determined by the MA dimensions (Classic ring size 38), the simulation demonstrated improved leaflet coaptation but with a residual lateral regurgitant orifice.…”
Section: Discussionmentioning
confidence: 99%
“…changed the relocation direction towards the anterior annulus 32,33) and 35,36) . The randomized CSTN trial found that mid-term survival and LV reverse remodeling did not significantly differ between restrictive annuloplasty repair and chordal-sparing valve replacement in patients with severely ischemic MR, but the incidence of recurrent MR and heart failure complications was greater after repair 37) .…”
Section: Moderate Mitral Regurgitation At Coronary Artery Bypass mentioning
confidence: 99%
“…However, catheter based bailout options in this patient‐cohort require sophisticated imaging diagnostics and high level operator experience and moreover these modalities are not yet clearly defined and standardized. Besides, best surgical approach for functional MR, in particular ischemic MR, remains controversial and is in general associated with both significant mortality and questionable long‐term durability and benefit 14,15 . Even with optimal MC and cardiac electronic devices therapy, results are not always as expected, and thus surgery becomes inevitable despite highest risk constellation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, best surgical approach for functional MR, in particular ischemic MR, remains controversial and is in general associated with both significant mortality and questionable long-term durability and benefit. 14,15 Even with optimal MC and cardiac electronic devices therapy, results are not always as expected, and thus surgery becomes inevitable despite highest risk constellation. This, therefore, calls for further exploration and refinement of existing predictors of device failure and patient selection criteria for the MC therapy.…”
Section: Introductionmentioning
confidence: 99%